1992
DOI: 10.2337/diacare.15.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of New Oral Hypoglycemic Agent CS-045 in NIDDM Subjects

Abstract: CS-045 improves insulin resistance, reduces insulinemia, lowers hepatic glucose production, and improves both fasting and postprandial glycemia in NIDDM subjects. CS-045 may represent a new therapeutic option for NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
198
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(215 citation statements)
references
References 17 publications
16
198
1
Order By: Relevance
“…* p = 0.001 vs before treatment, p < 0.05 vs placebo, ** p < 0.001 vs at the end of treatment Troglitazone treatment increased insulin sensitivity, as was seen from the lower glucose concentrations and HbA 1 c values in the face of reduced insulin requirements. This is a well known effect of troglitazone [6,7]. In the placebo group the metabolic control remained unchanged, although the insulin dose was increased.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…* p = 0.001 vs before treatment, p < 0.05 vs placebo, ** p < 0.001 vs at the end of treatment Troglitazone treatment increased insulin sensitivity, as was seen from the lower glucose concentrations and HbA 1 c values in the face of reduced insulin requirements. This is a well known effect of troglitazone [6,7]. In the placebo group the metabolic control remained unchanged, although the insulin dose was increased.…”
Section: Discussionmentioning
confidence: 79%
“…Thiazolidinediones are a new group of pharmaceutical agents, with both glucose and lipid lowering effects and the ability to reduce insulin resistance [6,7]. Thiazolidinediones possess affinity for peroxisome proliferator-activated receptor (PPAR)g [8±10].…”
mentioning
confidence: 99%
“…Liver (80 mg) was homogenized in 400 l homogenization buffer (0.25 mM sucrose containing 1 mM Tris (Cl Ϫ ), pH 7.5, and 1 mM EDTA) with one stroke of a loose-fitting hand-driven all-glass homogenizer and mitochondria and peroxisomes were isolated from fresh liver homogenates as described by Crane et al 20 Oxidation of [1-14 C]fatty acids to watersoluble products was measured as described by Watkins et al 21 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]lignoceric acid (C24:0), a very-long-chain fatty acid, and [1-14 C]palmitic acid (C16:0) were used to measure peroxisomal or mitochondrial fatty acid betaoxidation, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…11 These effects are associated with increased insulin sensitivity in hepatic and adipose tissue 11 and skeletal muscle. 12 The exact mechanisms underlying the insulin-sensitizing effects of TZD are not well defined. However, it is likely that multiple factors are involved.…”
mentioning
confidence: 99%
“…2 2,4-TZDs differ markedly from other antidiabetic drugs in that they are effective in normalizing glucose and lipid metabolism associated with insulin resistance and therefore are expected to be useful in treatment of type 2 diabetes mellitus and obesity. [3][4][5] Besides, it was reported that some 2,4-TZDs have been used as antihyperglycemic 6 and aldose reductase (AR) inhibitory agents with dual activity. 7 There is a great interest in 2,4-TZD derivatives as aldose reductase inhibitors (ARIs), 7,8 since they can be viewed as hydantoin bioisosters potentially free of the hypersensitivity reactions which are linked to the presence of the hydantoin system.…”
Section: Introductionmentioning
confidence: 99%